Insight into a single halobacterium using a dual‐bacteriorhodopsin system with different functionally optimized pH ranges to cope with periplasmic pH changes associated with continuous light illumination. Issue 3 (9th April 2013) - Fu, Hsu‐Yuan; Yi, Hsiu‐Ping; Lu, Yen‐Hsu; Yang, Chii‐Shen
Summary The light‐driven outward proton transporter assists energy production via an ATP synthase system best exemplified by the bacteriorhodopsin (BR) from Halobacterium salinarum, HsBR. As the only archaea able to survive in the resource‐limited ecosystem of the Dead Sea, Haloarcula marismortui has been reported to have a unique dual‐BR system, consisting of HmBRI and HmBRII, instead of only a single BR in a cell (solo‐BR). The contribution of this dual‐BR system to survival was investigated. First, native H. marismortui and H. salinarum cells were tested in water that had been adjusted to mimic the conditions of Dead Sea water. These archaea were shown to accumulate protons and reduce pH in their periplasmic regions, which disabled further proton transportation functionality in H. salinarum but not in H. marismortui. Then, pH‐dependent photocurrent measurements using purified BR proteins demonstrated that HsBR and HmBRI were functional at pH > 5.0 and that HmBRII was functional at pH > 4.0. Our results indicate that the dual‐HmBR system is composed of two BRs with different optimal functional pH ranges and together they maintain light‐driven proton transport activity under pH > 4.0, which might contribute the survival of H. marismortui under the acidic pH of the Dead Sea.